Cognitive impairment in anxiety disorders - B. A. Volel; D. S. Petelin; R. V. Akhapkin; A. A. Malyutina (Неврология, нейропсихиатрия, психосоматика, 2018)
Anxiety disorders are an important biomedical problem due to the high prevalence and significant negative impact on the quality of life and the course of concomitant somatic and neurological diseases. Cognitive impairment (CI) is one of the most intensively studied aspects of pathological anxiety. Impairments in attention, executive functions, memory, cognitive deficit, as well as abnormal cognitions and metacognitions are identified in anxiety disorders. Moreover, the treatment of the latter with the most frequently used drugs (antidepressants, atypical antipsychotics, anticonvulsants, tranquilizers) does not lead to a significant improvement in cognitive functions, and often contributes to their worsening. In this connection, in addition to psychotherapy, cognitive function-improving agents play a large role in treating anxiety diseases associated with cognitive dysfunction. Ginkgo Biloba extract (EGb 761, Tanakan®) that positively affects cognitive functions, especially in the domains of memory, concentration and attention deserves special attention.